Does mass media fuel, and easy credit facilitate, impulse buys? - Pasi Huovinen; Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2008)
This paper studies whether exposure to mass media and liking advertising are associated with an increased impulse buy tendency, and whether the availability of a credit card acts as a facilitating stimulus. It is found that impulse buys are positively associated with exposure to commercial television, but not to other forms of mass media. For females, liking advertising in general is positively associated with impulse buying; for males, having a preference for informative advertising is negatively associated with impulse buying. For both, credit card use facilitates the behavior. Besides being robust and statistically significant, these effects are qualitatively quite large.
Keywords: D12; E21; G21; L82; M37; 330; buying behavior; impulsiveness; mass media; advertising; credit cards; Konsumentenverhalten; Kauf; Kommunikationsmedien; Werbung; Kreditkarte; Finnland